The Influence Of Transformational Leadership, Personal Value And Organizational Commitment To The Performance Of Millerial Employees In Digital Era In Companies Internet Services Provider (Isp) In City Batam With Motivation As An Intervening Variable - Nurhatisyah nurhatisyah; Jemmy Rumengan; Bambang Satriawan; Sri Yanti; Ana Fahizah; Nolla Puspita Dewi (IAIC International Conference Series, 2021)
This study aims to analyze the effect of transformational leadership, personal value, and organizational commitment on the performance of millennial employees with motivation as an intervening variable on millennial employees of internet service provider companies in Batam. This type of research is associative causality. This research was conducted using a survey method by distributing questionnaires. The population of this research is three internet service provider companies domiciled in Batam Center. Data analysis methods used are descriptive statistical analysis and Partial Least Square (SEM-PLS) analysis. The analysis was assisted with the Smart PLS 3.0 program. The results of this study indicate that transformational leadership and organizational commitment significantly influence the performance of millennial employees of internet service provider companies in Batam while personal value has no significant effect. transformational leadership has no significant effect on motivation, while personal values and organizational commitment have a significant effect on motivation. The transformational leadership, personal value, and organizational commitment indirectly have insignificant effect on the performance of millennial employees of internet service provider companies in Batam with motivation as an intervening variable. transformational leadership has no significant effect on motivation, while personal values and organizational commitment have a significant effect on motivation. The transformational leadership, personal value, and organizational commitment indirectly have insignificant effect on the performance of millennial employees of internet service provider companies in Batam with motivation as an intervening variable. transformational leadership has no significant effect on motivation, while personal values and organizational commitment have a significant effect on motivation. The transformational leadership, personal value, and organizational commitment indirectly have insignificant effect on the performance of millennial employees of internet service provider companies in Batam with motivation as an intervening variable.